Algoritma dan Agama: Bagaimana Media Sosial Membentuk Pemahaman Keislaman Generasi Muda - Mutiara Fajriana; Adnan Priyamitra Sadeli; Nazwa; Fattah Ilyas Hawari; Abdul Fadhil (Yayasan Al-Afif, 2026)
The advancement of social media in the digital era has had a profound influence on how the younger generation understands Islamic teachings. Platforms such as TikTok, Instagram, and YouTube are no longer used solely for entertainment and communication, but have also become primary sources of religious information. Social media algorithms operate by tailoring content based on user activity and interests, thereby shaping repetitive and personalized patterns of religious information consumption. This exposes the younger generation more readily to a wide range of Islamic interpretations, from moderate to conservative and even extremist perspectives. At the same time, the role of religious authority has undergone a significant shift, moving away from traditional scholars and educational institutions toward digital influencers and Islamic content creators who deliver religious material in a concise, engaging, and accessible manner. Although social media offers greater accessibility to Islamic preaching and knowledge, the overly rapid and simplified presentation of religious information may lead to a superficial understanding that lacks depth and contextual grounding. Furthermore, the emergence of filter bubble and echo chamber phenomena causes users to predominantly consume information that aligns with their pre-existing views. Therefore, enhancing both digital literacy and religious literacy is essential so that the younger generation is able to engage with information critically and selectively, and is not easily swayed by hoaxes or extremist narratives on social media. When utilized appropriately, social media can serve as a positive, inclusive, and contextually relevant medium for Islamic outreach and education.